HUBUNGAN KOMPETENSI PEDAGOGIK DAN MINAT BACA DENGAN PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS 5 SEKOLAH DASAR DI GUGUS TLAJUNG UDIK KECAMATAN GUNUNGPUTRI KABUPATEN BOGOR - Karyawati, Sri; Siti Julaeha; Suroyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between teachers' pedagogical competence and students' reading interest with elementary school students' Indonesian language learning achievement. The study uses a quantitative approach with a correlational and regression design. The study population consists of all fifth-grade elementary school students in Gugus Tlajung Udik, Gunungputri District, Bogor Regency, totaling 585 students. A sample of 85 students was determined using proportional random sampling. Data were collected through questionnaires to measure teachers' pedagogical competence and students' reading interest, as well as Indonesian language achievement tests to measure student learning achievement. Data analysis was performed using descriptive and inferential statistics, including Pearson's correlation test and simple and multiple linear regression. The results showed that teachers' pedagogical competence had a positive and significant relationship with Indonesian language learning achievement. Students' reading interest also has a positive and significant relationship with Indonesian language learning achievement. Simultaneously, teachers' pedagogical competence and students' reading interest show a strong relationship with Indonesian language learning achievement. These findings indicate that Indonesian language learning achievement is influenced by the synergy between the quality of teachers' competence and students' reading interest. Based on these results, it can be concluded that improving elementary school students' Indonesian language learning achievement requires integrated efforts through strengthening teachers' pedagogical competence and developing students' reading interest in a sustainable manner. This study has implications for the development of Indonesian language learning practices and the strengthening of literacy culture in elementary schools.